Balanced Menu on Children's Abilities in Basic Motor Development and Early Childhood Intelligence - Candra Moh. Surya; Sony Kuswandi; Indri Rahmawati; Nasem Nasem (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims to improve the relationship between nutrition and basic motor development with the intelligence of RA children in Purwasari District. This study uses mixed research methods. The model used is a quantitative method as the main method. The population in this study were 558 RA students in Purwasari District with the sampling technique using the Slovin formula so that 90 samples were obtained as respondents. The data collection technique used in this study is through a quantitative questionnaire; as well as observation, interviews, and documentation for qualitative. While the data analysis technique uses the normality test (quantitative) and reduction (qualitative). The results showed that in addition to providing good nutrition for children, training, stimulus, health factors also support gross motor development and children's intelligence. Three instruments have a reliability value to be used as a data collection tool.